Marx’s Ideas About Freedom: An Exposition and Commentary - Villarmea, Karl James E. (Silliman Journal, 2022)
Long embedded in the history and tradition of democracy, the idea of freedom has played a conspicuous role, particularly, in modern human history. In the case of the rise of liberal democracy in the 20th century, the idea of freedom shaped up nationalist discourse and empowered dissident movements in Asia, Africa, and Latin America. It has also penetrated in the consciousness and inspired liberationist movements in non-western Eastern Europe, Soviet Union and China. The student movements that swept the XPSMEJOUIFMBUFTXFSFJOQBSUBMTPTQBSLFECZUIFRVFTUGPS freedom. Indeed one could argue with David Harvey that freedom is fundamental and a central value of human civilization. What is of import and relevant in contemporary public EJTDPVSTFJTUIBUUIFJEFBPGGSFFEPNIBTBDRVJSFEBUUFOUJPOBOE appropriation from different sectors of the society, may it be cultural, political, economic or even military, as in the case of former US 1SFTJEFOU(FPSHF8#VTI5IVT UIFSFBSFGVOEBNFOUBMRVFTUJPOT that could be asked: What is freedom? Whose freedom? To whose end does freedom serve? This paper attempts to contribute to this discussion, with the intent to view the subject matter differently. In this project, I intend to offer a Marxian perspective. Although I will largely elucidate and comment on Marx’s ideas about freedom, the larger intent of the project is to contribute to the discussion and to offer ways in which to think and enact freedom for contemporary times.